THE EFFECT OF JIGSAW TECHNIQUE ON THE ABILITY OF THE SECOND YEAR STUDENTS OF MTS KOTA INTAN IN COMPREHENDING DESCRIPTIVE TEXTS - Ratna Dewi; Effendy Gultom; Rumiri Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The objective of this research is to find out whether there is a significant effect of Jigsaw technique on the ability of the second year students of MTs Kota Intan in comprehending descriptive texts. This is a pre-experimental research with one group pre-test, treatment and post-test design. There are two classes in the first year. Class VIII A in the first semester of academic year 2018/2019 that consist of 25 students are chosen as the sample by using cluster random sampling technique. The instrument of the test is in the form of multiple choices which consist of 25 items about descriptive texts. To collect the needed data the treatments were conducted for six times. The students’ scores were analyzed by using Microsoft excel 2010 and SPSS (Statistical Product and Service Solutions) version 23.00 for windows. The results of the data analysis show that the mean score of the pre-test is 59.36 and the mean score of the post-test is 70.40. It means that the value of t-test (7.440) is higher than t-table (2.064) at 5% the significance level. Therefore, the alternative hypothesis (H1) of this research is accepted. In other words, there is a significant effect of Jigsaw technique on the second year students of MTs Kota Intan in comprehending descriptive texts. The implication of this finding is to be beneficial for the teacher in teaching and learning English especially in teaching reading.Keywords: Effect, Jigsaw Technique, Reading Comprehension, Descriptive Text